2006
DOI: 10.1102/1470-7330.2006.0013
|View full text |Cite
|
Sign up to set email alerts
|

Unusual lung tumours: an illustrated review of CT features suggestive of this diagnosis

Abstract: This review presents an imaging-centred approach to the diagnostic challenge of uncommon lung tumours in adults. Emphasis is placed on features that may be used to differentiate these tumours including fat content, tumour site, multifocality, calcification and predominant pattern of involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 54 publications
0
26
0
Order By: Relevance
“…ACC ACC is the most common salivary-type tumor of large airways and the second common primary tracheal tumor with a prevalence of 0.04-0.2% (19). It should be considered as differential diagnosis, especially in younger adults with tumors in trachea and/or large bronchi (40)(41)(42). Most studies reported female predominance and no association with smoking (43).…”
Section: Salivary Glands Malignant Tumorsmentioning
confidence: 99%
See 3 more Smart Citations
“…ACC ACC is the most common salivary-type tumor of large airways and the second common primary tracheal tumor with a prevalence of 0.04-0.2% (19). It should be considered as differential diagnosis, especially in younger adults with tumors in trachea and/or large bronchi (40)(41)(42). Most studies reported female predominance and no association with smoking (43).…”
Section: Salivary Glands Malignant Tumorsmentioning
confidence: 99%
“…However, nodules without these findings may be difficult for distinguishing from malignancies with CT alone. Postobstructive pneumonia or atelectasis can be present (Figure 8) (13,40,57). Hamartoma typically shows little or no radiotracer uptake on FDG PET.…”
Section: Hamartomasmentioning
confidence: 99%
See 2 more Smart Citations
“…Pulmonary hamartoma is the third most frequent cause of solitary pulmonary nodules with an overall prevalence of up to 5.7% (1), and chondromatous hamartoma is the most common type of pulmonary hamartoma (2). Masses are composed of abnormal mixtures of epithelial and mesenchymal elements, such as cartilage, fat, fibromyxoid tissue, smooth muscle, and bone (3,4).…”
Section: Introductionmentioning
confidence: 99%